Representation of Teacher in Andrea Hirata’s Novel Guru Aini: A Study of Literary Psychology - Evi Chamalah; Reni Nuryyati; S. T. Nurbaya (Journal of Advanced Multidisciplinary Research, 2020)
Novel is one of literary works that is quite enjoyed by people. Novel has an important position in describing the reality of life through its storylines. One of them is Guru Aini novel by Andrea Hirata. The novel, which was just published in 2020, told about a teacher who workedin a remote island in Indonesia. The author's view of the teacher as an educator who could be represented by this literary work is constructed in a novel. Based on this, the study aimed to determine the representation of teachers in the Guru Aini novel by Andrea Hirata. The analysis in the research was conducted through the dimensions of literary psychology. The analysis in this study focused on the role of the teacher as an educator in a literary work. The results in this study indicated that the teacher in the novel Guru Aini by Andrea Hirata was represented in a positively charged construction. In this study, it was found that several teacher representations appeared in the novel, namely the representation of the teacher as an individual status, the representation of the teacher as the status of the teaching force, the representation of the teacher as an educator in the community, the representation of the psychological condition of the teacher, and the representation of the teacher's personality in the novel Guru Aini by Andrea Hirata.